Epigallocatechin gallate Mucoadhesive Gingival Patch as Potential Biomaterial to Regulate Macrophage and Lymphocyte Cells in Periodontitis: A Review - Sidarningsih, Sidarningsih; Diyatri, Indeswati; Pratiwi, Reinaya Tifa; Nabilla, Jihan Hijriya; Yuliati, Yuliati; Ridwan, Rini Devijanti (Indonesian Journal of Dental Medicine, 2022)
Background: Periodontitis is a periodontal disease that affects more than 743 million peopleworldwide and causes damage to the periodontal ligament and alveolar bone. One of the bacteriathat can cause periodontitis is Porphyromonas gingivalis (P.gingivalis). P. gingivalis has virulence factors that can damage the periodontal tissue. Treatment of periodontitis is in the form of non- surgical therapy such as scaling and root planning and some cases, doxycycline can be given as adjunctive therapy after scaling and root planing. Epigallocatechin gallate (EGCG) is one of the catechins found in green tea and has anti-bacterial properties. Purpose: The study aimed to describe the potency of the mucoadhesive gingival patch with EGCG green tea against the number of macrophage cells and lymphocyte cells during periodontitis through narrative review. Review: Mucoadhesive gingiva patch loaded with EGCG has the advantages such as maintaining drug bioavailability, non-invasive, and optimizing drug distribution. Using a mucoadhesive gingiva patch with EGCG can reduce macrophage and lymphocyte cells by inhibiting lipopolysaccharide, a virulence factor of P. gingivalis. Inhibited lipopolysaccharide will inhibit pro-inflammatory cytokines such as TNF-α and IL-6. Macrophage and lymphocyte cells will reduce due to the inhibition of pro inflammatory cytokines. Conclusion: Mucoadhesive gingiva patch with EGCG green tea potentially to decreased macrophage and lymphocyte cells in periodontitis.